2014
DOI: 10.1051/0004-6361/201423385
|View full text |Cite
|
Sign up to set email alerts
|

Alfvénic waves in polar spicules

Abstract: Context. For investigating spicules from the photosphere to coronal heights, the new Hinode/SOT long series of high-resolution observations from space taken in CaII H line emission offers an improved way to look at their remarkable dynamical behavior using images free of seeing effects. They should be put in the context of the huge amount of already accumulated material from groundbased instruments, including high-resolution spectra of off-limb spicules. Aims. Both the origin of the phenomenon and the signific… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 47 publications
(81 reference statements)
0
14
0
Order By: Relevance
“…It is observed that Type-II spicules have axial-rotation spin with rotation speeds of 25-30 km s -1 (De Pontieu et al 2012). From analysis of the proper motions in Type-II spicules at the limb in a polar coronal hole in a Hinode/SOT Ca II H movie, Tavabi et al (2015) have recently presented evidence that the spin is from untwisting of the magnetic field like the untwisting we observe in our big jets. Moore et al (2011) proposed that Type-II spicules are miniature versions of the large EUV/X-ray jets in coronal holes, made in the same way by interchange reconnection of emerging and blowout-erupting granule-size closed magnetic bipoles ( 1000 km in diameter) with the ambient feet of the coronal magnetic field rooted in the magnetic network in quiet regions and corona holes.…”
Section: Summary and Disscussionmentioning
confidence: 56%
See 1 more Smart Citation
“…It is observed that Type-II spicules have axial-rotation spin with rotation speeds of 25-30 km s -1 (De Pontieu et al 2012). From analysis of the proper motions in Type-II spicules at the limb in a polar coronal hole in a Hinode/SOT Ca II H movie, Tavabi et al (2015) have recently presented evidence that the spin is from untwisting of the magnetic field like the untwisting we observe in our big jets. Moore et al (2011) proposed that Type-II spicules are miniature versions of the large EUV/X-ray jets in coronal holes, made in the same way by interchange reconnection of emerging and blowout-erupting granule-size closed magnetic bipoles ( 1000 km in diameter) with the ambient feet of the coronal magnetic field rooted in the magnetic network in quiet regions and corona holes.…”
Section: Summary and Disscussionmentioning
confidence: 56%
“…See Moschou et al (2013) for evidence of an upward force in large jets observed in AIA He II 304 Å movies.] Another candidate for the energy-transfer process is turbulent cascade of the wave to Alvenic waves of progressively higher wavenumbers, finally dissipating at the high-wavenumber end of the cascade to heat the plasma in the cascading turbulence (e.g., Hollweg 1984;van Ballegooijen et al 2011). We expect that physically realistic numerical modeling of the generation and non-linear propagation of the magnetic-untwisting waves in polar coronal jets will be required to establish how these waves lose energy in the inner corona.…”
Section: Summary and Disscussionmentioning
confidence: 99%
“…The solar corona contains transverse, incompressible oscillations in the magnetic field and plasma velocity (Banerjee et al 1998;Tomczyk et al 2007;Jess et al 2009;McIntosh 2012), but whether they should be called "Alfvén waves" is still a matter of debate (e.g., Mathioudakis et al 2013). More specifically, spicules and jets themselves seem to contain torsional or kink motions that could have an Alfvénic character (Kukhianidze et al 2006;De Pontieu et al 2014b;Tavabi et al 2015). There is also evidence for longitudinal compressive wavesi.e., fluctuations in density and the velocity component parallel to the wavenumber vector-that may or may not follow the ideal MHD magnetoacoustic dispersion relations (Ofman et al 1999;Krishna Prasad et al 2012;Threlfall et al 2013;Miyamoto et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…One may interpret these components as the components of a rotating spicule. Twisty motions have already been reported with a velocity of about 25 kms -1 (De Pontieu et al 2014a;Tavabi et al 2015b) and they are predicted by magnetic vortex plasma simulation (Kitiashvili et al 2013;Gonzalez-Aviles et al 2017). An explosive event could eject plasma in all directions and produce equal red-and blueshifts, as for a bi-directional jets (Tavabi et al 2015a).…”
Section: Discussionmentioning
confidence: 77%